Regression Analysis for the Adsorption Isotherms of Natural Dyes onto Bamboo Yarn - Tengku Khamanur Azma, Tg. Mohd Zamri; Mimi Sakinah, A. M.; Zularisam, A. W. (IRJET, 2017)
The adsorption of three natural dyes which extracted from Turmeric, Red Dragon Fruit Peel (RDFP) and Blue Butterfly Pea Flower (BBPF) onto bamboo yarn was studied. The results revealed that the potential of selected natural dyes on replacing the existing synthetic dyes in industry and the synthetic fibre with the natural fibre (bamboo yarn). Equilibrium isotherms were analyzed using the Langmuir, Freundlich, and Temkin isotherms. In order to determine the best-fit isotherm for each adsorption of natural dye on bamboo yarn, four error analysis methods were used to evaluate the data: the squares of the errors (SSE), residual root mean square error (RMSE), chi- square test, χ2 and coefficient of determination, R2 statistic test for determination of a non-linear model. Results indicated that the good fit of Temkin models for Turmeric dye, Freundlich model for RDFP dye and Langmuir model for BBPF dye with the higher value of coefficient of determination, R2 but lower value of squares of the errors (SSE), residual root mean square error (RMSE) and chi- square test, χ2.